2020
DOI: 10.1002/jor.24964
|View full text |Cite
|
Sign up to set email alerts
|

Chronic subacromial impingement leads to supraspinatus muscle functional and morphological changes: Evaluation in a murine model

Abstract: Muscle atrophy and fatty infiltration have been directly correlated with higher rates of incomplete or failed healing following surgical repair of the rotator cuff. The purpose of this study was to evaluate clinically relevant functional and morphological changes in the supraspinatus muscle at various time points in this model of rotator cuff tendinopathy. Subacromial impingement was induced in 47, male C57BL/6 mice (total 94 limbs) by implantation of a metal clip in the subacromial space. Specimens were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Our data demonstrate that 3D muscle volumetry should be preferred in patients with full-thickness SSP tendon tears when the muscle volume needs to be quantified preoperatively in order to estimate the postoperative success rate after tendon repair procedures. This is in accordance with previous studies [ 17 ] and is important since various previous experimental and clinical studies have shown that significant SSP muscle atrophy is an important adverse prognostic factor affecting patients’ outcomes in addition to other conditions, e.g., fatty infiltration or severe tear size [ 8 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our data demonstrate that 3D muscle volumetry should be preferred in patients with full-thickness SSP tendon tears when the muscle volume needs to be quantified preoperatively in order to estimate the postoperative success rate after tendon repair procedures. This is in accordance with previous studies [ 17 ] and is important since various previous experimental and clinical studies have shown that significant SSP muscle atrophy is an important adverse prognostic factor affecting patients’ outcomes in addition to other conditions, e.g., fatty infiltration or severe tear size [ 8 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Discussionsupporting
confidence: 92%
“…A rat‐walking apparatus system was used to evaluate the recovery of locomotor functions by comparing the experimental foot (left hind in the system, LH) with the contralateral healthy foot (right hind in the system, RH) at week 10. [ 45,46 ] The footprint intensity and foot pressure of transected nerve rats were significantly lower than those of sham group, and no statistical difference was noticed among nerve anastomosis groups for the foot pressure (Figure 6C). Rat body wobble was reflected by stance trace (Figure 6D).…”
Section: Resultsmentioning
confidence: 95%
“…Recent advancements in the development and use of a mouse rotator cuff impingement model using a consistent titanium microvascular surgical clip have simplified the study of the molecular mechanisms underlying rotator cuff injury and healing due to extrinsic impingement. 9,10,12,41,42 Titanium has similar qualities to bone, and the titanium clips in our model are easy to insert and remove, which make the mouse model easy to replicate. In the current study, we used the same model to induce supraspinatus tendinopathy, then removed the clip under the acromion to simulate acromioplasty and initiate recovery.…”
Section: Discussionmentioning
confidence: 99%
“…To ensure consistent joint loading during postoperative daily cage activity, all animals underwent bilateral surgery as per the design of previous studies. 9,10,12,41,42 All animals were returned to normal cage activity immediately after surgery in specific pathogen-free cages with standardized cage amenities (feed, bedding, and water). High-resolution radiographs were obtained at the 4-week time point to confirm the subacromial position of the implanted surgical clip.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation